THE EFFECT OF GIVING PINEAPPLE PEEL EXTRACT (Ananas comocus L. Merr) IN DRINKING WATER ON THE PERFORMANCE OF JOPER CHICKEN - N. L. S., Widiasih; Dewi, G. A. M. K.; Sriyani, N. L. P. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aims to determine the effect of giving pineapple peel extract through drinking water on the performance of joper chickens. This research was conducted for six weeks. The design used was a completely randomized design (CRD) with 4 treatments and 5 replications. Each replication used 3 joper chickens aged 2 weeks with a homogeneous body weight of 100.31 ± 11.4 g, so that 20 experimental units were obtained with a total of 60 joper chickens to be used. The treatment consisted of P0 (Joper chickens were given drinking water without pineapple peel extract as a control), P1 (Joper chickens were given drinking water with 6% pineapple peel extract in 1 liter of water), P2 (Joper chickens were given 8 % pineapple peel extract in 1 liter of water), and P3 (Joper chickens were given drinking water with 10% pineapple peel extract in 1 liter of water). The variables observed were total ration consumption, total drinking water consumption, final body weight, body weight gain, and feed conversion ratio (FCR). The results of this study showed that the initial body weight in treatments P1, P2, and P3 was not significantly different (P >0.05) lower than in treatment P0, followed by ration consumption , drinking water consumption , final body weight, weight gain, and feed conversion ratio (FCR) in treatments P1, P2, and P3 was not significantly different (P > 0.05) from treatment P0. The results of this study can be concluded that administration of pineapple peel extract at levels of 6%, 8%, and 10% can increase  ration consumption, drinking water consumption , final body weight, weight gain, and decrease feed conversion ratio (FCR).